DETERMINANTELE ADAPTĂRII PSIHOSOCIALE A ADOLESCENŢILOR LA SISTEMUL DE INSTRUIRE UNIVERSITAR - USM ADMIN (Moldova State University, 2007)
Psychological adaptation of students to a system of university education is a complicated and multilateral process which requires immediate consideration. It is important to analyze all the factors of students 'adaptation / non- adaptation to new conditions. The process of adaptation depend on: 1) one's capability to get adapted to changes and new conditions which are supposed to exist in the system of education 2) capability of the system itself to get changed in its turn, or to offer the students the best possible conditions for adaptation.